Plan de negocios para la comercialización de la longaniza San Carlos - Medina Mure, Andrea Narcisa (2023)
This investigation was carried out with the purpose of carrying out a business plan for the commercialization of Longaniza San Carlos in Portoviejo city. Considering the contribution that this document represents for the company "San Carlos" in the development of its functions, providing an overview of all aspects involved in the commercialization of the product. For which three phases were developed, in the first instance a market study was needed, the same one that demanded the application of the questionnaire in conjunction with the survey for the proper data collection, which provided the criteria, customs and behaviors of consumer purchase determining as a response the level of acceptance of the product by consumers. In the second instance, a technical-operative study was required in which materials, supplies and costs necessary for the production and distribution of the product were established. Finally, the third stage consisted of an economic-financial study allowing to know the viability and profitability of the present project, obtaining as a result an TIR with a positive percentage and greater than the discount percentage with an investment recovery of about one year and two months.